2014
DOI: 10.3791/51576
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Rodent Assay for Quantifying Male Germ Cell Mutant Frequency

Abstract: De novo mutations arise mostly in the male germline and may contribute to adverse health outcomes in subsequent generations. Traditional methods for assessing the induction of germ cell mutations require the use of large numbers of animals, making them impractical. As such, germ cell mutagenicity is rarely assessed during chemical testing and risk assessment. Herein, we describe an in vivo male germ cell mutation assay using a transgenic rodent model that is based on a recently approved Organisation for Econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Comparison of ENU-mutagenesis using tandem repeat loci versus the TGR assay at the same dose shows that the TGR assay consistently reports a higher fold increase in mutation frequency following ENU exposure [12,19,36,37]. It has been demonstrated using ENU that the mutation response of ESTRs in sperm appears to plateau at a 3-fold increase [19], whereas ENU-induced point mutations plateau at a 5-fold increase [36,14].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Comparison of ENU-mutagenesis using tandem repeat loci versus the TGR assay at the same dose shows that the TGR assay consistently reports a higher fold increase in mutation frequency following ENU exposure [12,19,36,37]. It has been demonstrated using ENU that the mutation response of ESTRs in sperm appears to plateau at a 3-fold increase [19], whereas ENU-induced point mutations plateau at a 5-fold increase [36,14].…”
Section: Discussionmentioning
confidence: 90%
“…It has been demonstrated using ENU that the mutation response of ESTRs in sperm appears to plateau at a 3-fold increase [19], whereas ENU-induced point mutations plateau at a 5-fold increase [36,14]. Similarly, we found that the mutation induction observed at the microsatellite locus following both the ENU (2.4-fold) and BaP (2.3-fold) exposures were lower than the induced lacZ mutation frequency measured using the TGR assay (∼5-fold) in the same samples (ENU published in [16,36]; BaP unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of transgenic rodent (TGR) models to investigate the induction of mutations in germ cells involves many considerations both in terms of the timing for sample collection and in the methods used to isolate DNA. This topic has been covered elsewhere [ 10 ].…”
Section: Introductionmentioning
confidence: 99%